Segmental Phonology of English and Chhintang: A Contrastive Analysis with Pedagogical Implications - Rai, Ichha Purna (Education and Development, 2024)
This paper attempts to compare and contrast the segmental phonology of English and the Chhintang language. English data were taken from secondary sources, whereas Chhintang data were taken from primary sources. Segmental phonology deals with the study of segments of human speech, which are basically consonants and vowels. This paper contributes to a contrastive analysis between consonants and vowels found in English and Chhintang based on structural linguistics. I explored the Chhintang segmental sounds from my own field work (2022, March). Then it suggests some pedagogical implications. The major findings of this paper include the different numbers in the inventory of sounds, aspiration as allophones and phonemes, sounds found in one language but not found in another, vowel length, and so on.